2011
DOI: 10.1002/chp.20148
|View full text |Cite
|
Sign up to set email alerts
|

Peering Inside the Clock: Using Success Case Method to Determine How and Why Practice-Based Educational Interventions Succeed

Abstract: The study shows that (1) the appropriate target of an educational intervention may be a team rather than an individual, (2) implementing even relatively simple practice guidelines can be a complex process, and (3) change requires scientific and practical knowledge. A richer understanding of implementation mechanisms and contextual factors is needed to guide educational planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 23 publications
2
27
0
Order By: Relevance
“…Several case studies have demonstrated that education, specifically Performance Improvement (PI) CME, improves clinical practice. [28][29][30][31][32][33][34][35] However, to our knowledge, data do not exist regarding the use of the PI CME format in the specialty of dermatology. PI CME helps physicians evaluate their practice and implement evidencebased strategies to overcome identified gaps, then remeasure their performance after these strategies have been implemented in their practice.…”
mentioning
confidence: 63%
“…Several case studies have demonstrated that education, specifically Performance Improvement (PI) CME, improves clinical practice. [28][29][30][31][32][33][34][35] However, to our knowledge, data do not exist regarding the use of the PI CME format in the specialty of dermatology. PI CME helps physicians evaluate their practice and implement evidencebased strategies to overcome identified gaps, then remeasure their performance after these strategies have been implemented in their practice.…”
mentioning
confidence: 63%
“…The mechanism through which the activity contributed to behavior change varied from helping learners develop new skills to providing practical tools, and depended on the clinical context, such as ability to customize electronic health records systems and prior experience using clinical data. See the article by Olson and colleagues 20 in this supplement for more detailed information.…”
Section: Scm Study Resultsmentioning
confidence: 96%
“…McKeithen and colleagues 11 described how a comprehensive needs assessment was conducted and how the data from the assessment were used to plan and evaluate the educational activities of the initiative. Olson and colleagues 12 described the implementation and results of a relatively new approach to evaluation, the Success Case Method, and Shershneva and Apply and improve educational interventions using evidence-based adult and organizational principles in appropriate contexts (learners, content, and settings) that produce expected results for the physician learners and the organizations in which they work.…”
Section: Alliance Competency Area 2: Educational Interventionsmentioning
confidence: 97%